A method for rapidly preparing graphene
By pressing and molding the graphite oxide and flashing treatment, the problems of low yield, high cost and poor conductivity in the existing graphene preparation methods are solved, and a method for rapid preparation of highly conductive graphene is realized.
Patent Information
- Application Number
- CN202310240019.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-03-14
AI Technical Summary
Among the existing graphene preparation methods, the micromechanical peeling method has low yield, the chemical vapor deposition method has expensive reactants and dangerous operation, and the chemical peeling method has a long preparation period and poor product conductivity.
By pressing the graphite oxide and then performing flash burning, the oxygen-containing groups are quickly decomposed and removed at high temperature, reducing and peeling of the graphite layer is achieved, and graphene with excellent conductivity is obtained.
The rapid preparation of graphene is achieved, with a short production cycle and excellent conductivity, avoiding the problems of low yield, high cost and operational hazards in the existing methods.
Smart Images

Figure CN116332163B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene preparation, and in particular relates to a method for rapidly preparing graphene. Background Art
[0002] Existing methods for preparing graphene mainly include chemical vapor deposition, micromechanical exfoliation, chemical exfoliation, etc.
[0003] The micromechanical exfoliation method uses the adhesive force of tape to peel off flake graphite layer by layer through multiple pastings, and then pastes the tape with graphite flakes onto a target substrate such as a silicon wafer. Finally, the tape is removed with solvents such as acetone to obtain a single layer of graphene. This method has a simple operation process and high product quality, but low yield, and it is difficult to achieve large-area and large-scale preparation of graphene.
[0004] Chemical vapor deposition uses carbon-containing compounds such as methane as a carbon source to grow graphene through high-temperature decomposition on the surface of an organism. Although the graphene prepared by this method is of high quality and can be grown over a large area, the reactant methane required for the reaction is expensive and the experimental operation process is highly dangerous.
[0005] The chemical exfoliation method uses redox reactions to introduce functional groups on the carbon atoms of the graphite layer, increasing the interlayer spacing of the graphite, thereby weakening its interlayer interaction, and then separating the oxidized graphite layers layer by layer through ultrasound or rapid expansion to obtain oxidized graphene, and finally removing the oxygen-containing functional groups through chemical reduction or high-temperature reduction to obtain graphene. This method is currently an effective method for large-scale preparation of graphene, but the preparation cycle is long, and the oxidation, ultrasound and subsequent reduction processes often cause the loss of carbon atoms. The prepared graphene contains more defects, resulting in poor conductivity. Summary of the invention
[0006] The object of the present invention is to provide a method for rapidly preparing graphene. The method provided by the present invention has a short production cycle and can obtain graphene with excellent electrical conductivity.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for rapidly preparing graphene, comprising the following steps:
[0009] After pressing graphite oxide into shape, flash calcining is performed to obtain the graphene;
[0010] The temperature of the flash treatment is 1000-5000° C., and the insulation time is 5-500s.
[0011] Preferably, the oxygen content of the graphite oxide is 0.1-30%.
[0012] Preferably, the flash treatment is carried out in a protective atmosphere.
[0013] Preferably, the flash burning treatment is carried out under normal pressure.
[0014] Preferably, before the pressing and molding, the graphite oxide is ground; the particle size of the ground graphite oxide is 1 to 50 μm.
[0015] Preferably, the compression molding pressure is 18 to 24 MPa, and the holding time is 5 to 20 s.
[0016] Preferably, the heating rate to the flash treatment temperature is 90 to 300° C. / s.
[0017] Preferably, the flash treatment comprises:
[0018] The pressed graphite oxide is placed on a conductive carrier, both ends of the conductive carrier are connected to the positive and negative electrodes of a power source, and power is applied to perform a flash burning process.
[0019] Preferably, the conductive carrier comprises carbon paper, graphite sheet, molybdenum boat, tungsten boat or stainless steel sheet;
[0020] The thickness of the conductive carrier is 0.1-10 mm.
[0021] Preferably, the current of the power supply is 1-500A.
[0022] The present invention provides a method for rapidly preparing graphene, comprising the following steps: pressing graphite oxide into shape, and then flashing the graphene to obtain the graphene; the temperature of the flashing treatment is 1000-5000°C, and the holding time is 5-500s. In the present invention, during the flashing treatment, the energy of the graphite oxide can be instantly increased to produce a strong thermal shock, and the thermal motion of oxygen-containing groups such as hydroxyl and carboxyl groups on the carbon layer can be stimulated, and the reduction of the single-layer graphite oxide can be achieved through the rapid decomposition and release of the oxygen-containing groups; at the same time, the released oxygen can destroy the van der Waals force between the graphite layers, thereby achieving the peeling between the graphite layers, and finally obtaining graphene. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the SEM image of the graphene obtained in Example 1;
[0024] Figure 2 This is the SEM image of the graphene obtained in Example 2;
[0025] Figure 3 This is the SEM image of the graphene obtained in Example 3;
[0026] Figure 4 This is the SEM image of the graphene obtained in Comparative Example 1;
[0027] Figure 5 is the SEM image of graphite oxide;
[0028] Figure 6 TEM image of graphene obtained in Example 1;
[0029] Figure 7 is the XRD pattern of graphite oxide;
[0030] Figure 8 is the XRD pattern of graphene obtained in Example 1;
[0031] Fig. 9 This is a rate performance diagram of a sodium ion half-cell assembled using graphene obtained in Example 1 as electrode material;
[0032] Fig.10 This is a cycle performance diagram of a sodium ion half-cell assembled using graphene obtained in Example 1 as electrode material;
[0033] Fig.11 It is a schematic diagram of the device in the flash burning process of the present invention. DETAILED DESCRIPTION
[0034] The present invention provides a method for rapidly preparing graphene, comprising the following steps:
[0035] After pressing graphite oxide into shape, flash calcining is performed to obtain the graphene;
[0036] The temperature of the flash treatment is 1000-5000° C., and the insulation time is 5-500s.
[0037] In the present invention, unless otherwise specified, all raw materials are commercially available products well known to those skilled in the art.
[0038] In the present invention, the oxygen content of the graphite oxide is preferably 0.1 to 30%, more preferably 5 to 25%, and even more preferably 10 to 20%.
[0039] Before the press molding, the present invention preferably further comprises grinding the graphite oxide.
[0040] In the present invention, the grinding time is preferably 10 min. In the present invention, the particle size of the ground graphite oxide is preferably 1 to 50 μm, more preferably 5 to 40 μm, and more preferably 20 to 30 μm. In the present invention, the grinding is preferably performed in a mortar.
[0041] In the present invention, the compression molding pressure is preferably 18 to 24 MPa, more preferably 19 to 23 MPa, and more preferably 20 to 22 MPa; the holding time is preferably 5 to 20 s, more preferably 8 to 18 s, and more preferably 10 to 15 s.
[0042] In the present invention, the diameter of the graphite oxide sheet obtained after the compression molding is preferably 12 to 13 mm, and the thickness is preferably 0.1 cm; the mass of a single graphite oxide sheet is preferably 20 to 100 mg.
[0043] In the present invention, the temperature of the flash treatment is 1000-5000°C, more preferably 1500-4000°C, and more preferably 2000-3000°C; the heating rate to the flash treatment temperature is preferably 90-300°C / s, more preferably 100-250°C / s, and more preferably 150-200°C / s; the holding time is 5-500s, more preferably 50-400s, and more preferably 100-300s.
[0044] In the present invention, the flash treatment is preferably carried out in a protective atmosphere; the protective atmosphere is preferably nitrogen.
[0045] In the present invention, the flash treatment is preferably performed under normal pressure.
[0046] In the present invention, the flash treatment preferably includes:
[0047] The pressed graphite oxide is placed on a conductive carrier, both ends of the conductive carrier are connected to the positive and negative electrodes of a power source, and power is applied to perform a flash burning process.
[0048] In the present invention, the conductive carrier preferably includes carbon paper, graphite sheet, molybdenum boat, tungsten boat or stainless steel sheet. In the present invention, the thickness of the conductive carrier is preferably 0.1 to 10 mm, more preferably 1 to 9 mm, more preferably 2 to 8 mm. In a specific embodiment of the present invention, the size of the carbon paper is preferably 10 cm*5 cm*1 mm; the positive and negative electrodes of the power supply are preferably connected to the short sides of the carbon paper, respectively. The schematic diagram of the device provided by the present invention is as follows Fig.11 shown.
[0049] In the present invention, the current applied is preferably 1 to 500A, more preferably 50 to 400A, and even more preferably 100 to 300A.
[0050] In order to further illustrate the present invention, a method for rapidly preparing graphene provided by the present invention is described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0051] Example 1
[0052] Graphite oxide with an oxygen content of 20% was placed in a mortar and ground for 20 minutes. The obtained graphite oxide (particle size of 20-30 μm) was placed in a mold and pressed at a pressure of 15 MPa for 20 seconds to obtain graphite oxide sheets with a diameter of 12 mm and a thickness of 0.1 cm (mass of about 51 mg).
[0053] The obtained graphite oxide sheet was placed on a carbon paper with a size of 10cm*5cm*1mm, and the short sides of the carbon paper were connected to the positive and negative electrodes of the power supply respectively. The paper was powered on for flash treatment under normal pressure and nitrogen atmosphere, wherein the current was 160A, the flash treatment temperature was 1300°C, the heating rate was 90°C / s, and the holding time was 100s to obtain graphene.
[0054] Example 2
[0055] Graphite oxide with an oxygen content of 20% was placed in a mortar and ground for 20 minutes. The obtained graphite oxide (particle size of 20-30 μm) was placed in a mold and pressed at a pressure of 15 MPa for 20 seconds to obtain graphite oxide sheets with a diameter of 12 mm and a thickness of 0.1 cm (mass of about 51 mg).
[0056] The obtained graphite oxide sheet was placed on a carbon paper with a size of 10cm*5cm*1mm, and the short sides of the carbon paper were connected to the positive and negative electrodes of the power supply respectively. The flash treatment was performed by power-on under normal pressure and nitrogen atmosphere, wherein the current was 150A, the flash treatment temperature was 1200°C, the heating rate was 90°C / s, and the insulation time was 100s to obtain graphene.
[0057] Example 3
[0058] Graphite oxide with an oxygen content of 20% was placed in a mortar and ground for 20 minutes. The obtained graphite oxide (particle size of 20-30 μm) was placed in a mold and pressed at a pressure of 15 MPa for 20 seconds to obtain graphite oxide sheets with a diameter of 12 mm and a thickness of 0.1 cm (mass of about 51 mg).
[0059] The obtained graphite oxide sheet was placed on a carbon paper with a size of 10cm*5cm*1mm, and the short sides of the carbon paper were connected to the positive and negative electrodes of the power supply respectively. The paper was powered on for flash burning under normal pressure and nitrogen atmosphere, wherein the current was 180A, the flash burning temperature was 1500°C, the heating rate was 100°C / s, and the holding time was 100s to obtain graphene.
[0060] Example 4
[0061] Graphite oxide with an oxygen content of 20% was placed in a mortar and ground for 20 minutes. The obtained graphite oxide (particle size of 20-30 μm) was placed in a mold and pressed at a pressure of 15 MPa for 20 seconds to obtain graphite oxide sheets with a diameter of 12 mm and a thickness of 0.1 cm (mass of about 51 mg).
[0062] The obtained graphite oxide sheet was placed on a carbon paper with a size of 10cm*5cm*1mm, and the short sides of the carbon paper were connected to the positive and negative electrodes of the power supply respectively. The paper was powered on for flash treatment under normal pressure and nitrogen atmosphere, wherein the current was 200A, the flash treatment temperature was 2500°C, the heating rate was 200°C / s, and the holding time was 50s to obtain graphene.
[0063] Comparative Example 1
[0064] Graphite oxide with an oxygen content of 20% was placed in a mortar and ground for 20 minutes. The obtained graphite oxide (particle size of 20-30 μm) was placed in a mold and pressed at a pressure of 15 MPa for 20 seconds to obtain graphite oxide sheets with a diameter of 12 mm and a thickness of 0.1 cm (mass of about 51 mg).
[0065] The obtained graphite oxide sheet was placed on carbon paper with a size of 10cm*5cm*1mm, and then placed in a tubular furnace for high-temperature carbonization at 1500°C under normal pressure and nitrogen atmosphere with a heating rate of 30°C / min and a holding time of 10h to obtain a sample.
[0066] Performance Testing
[0067] Test Example 1
[0068] The graphene and graphite oxide raw materials obtained in Examples 1 to 3 and Comparative Example 1 were tested by scanning electron microscopy, and the obtained SEM images are as follows: Figures 1 to 5 As shown, Figure 1 For Example 1, Figure 2 For Example 2, Figure 3 For Example 3, Figure 4 For comparative example 1, Figure 5 For graphite oxide, Figures 1 to 5 It can be seen that the graphite oxide is a whole block structure without an obvious layered structure; in the comparative example, the graphite oxide is not completely peeled off, and the block structure of the graphite oxide still exists; the graphene obtained in the present invention has a layered wrinkled structure, and the single-layer graphene sheet is very thin.
[0069] Test Example 2
[0070] The graphene obtained in Example 1 was tested by transmission electron microscopy, and the obtained TEM image is as follows: Figure 6 As shown, from Figure 6It can be seen that the graphene shows a transparent structure, indicating that the thickness of the graphene is very thin. Wrinkles can be observed in some areas of the sample, which is caused by the overlapping of graphene sheets or the curling of the edge areas. At the same time, the graphene surface texture is obvious, flat and orderly.
[0071] Test Example 3
[0072] The graphene and graphite oxide raw materials obtained in Example 1 were subjected to X-ray diffraction test, and the obtained XRD pattern was as follows: Figure 7 and 8 As shown, Figure 7 is graphite oxide, Figure 8 For Example 1, from Figures 7-8 It can be seen that the graphene provided by the present invention has a diffraction peak near 2θ of 23°, the peak becomes wider and the intensity weakens, and is very close to 2θ of graphite of 26°, indicating that the experimental product is graphene; after graphite oxide is converted into graphene, Figure 7 The (001) crystal plane diffraction peak in the graphite completely disappears, indicating that the graphite oxide has been completely reduced to a single layer of graphene; the broadening of the graphene diffraction peak is due to the interlayer exfoliation of the single layer of graphite, and the reduction of the single sheet size, the decrease of the crystal structure integrity and the increase of disorder.
[0073] Test Example 4
[0074] The graphene obtained in Example 3 was used as the electrode active material to test the electrochemical performance;
[0075] Graphene, acetylene black, and PVDF solution (dissolved in polypyrrolidone) with a mass concentration of 2% are mixed in a ratio of 8:1:1, mixed until viscous, applied to the copper current collector, and then dried in a vacuum drying oven at 110°C for 12 hours, and a pole piece with a diameter of 12 mm is cut out with a cutting machine, weighed, and the graphene loading on the pole piece is calculated to be about 2 mg; placed in an oven and dried at 60°C for 6 hours to obtain a positive electrode;
[0076] In an argon-protected glove box, a 2032-type button-type sodium ion half-cell was assembled with a sodium metal sheet as the negative electrode, a glass fiber membrane as the separator, and 1 mol / L NaPF6 (EC:DMC=1:1) as the electrolyte.
[0077] The half-cell was tested in constant current charge and discharge mode with a current density of 0.05A / g to 10A / g and a voltage range of 0.01 to 3V. The test curves are shown in Figure 2. Fig. 9 and 10 As shown;
[0078] in Fig. 9 is the rate performance diagram, from Fig. 9It can be seen that the specific capacity at a current density of 0.05A / g is 200mAh / g, and the specific capacity at a current density of 10A / g is 30mAh / g, which has excellent rate performance;
[0079] Fig.10 The cycle performance curve is Fig.10 It can be seen that after 100 cycles at 0.1 A / g, there is still a specific capacity of 100 mAh / g, indicating that the material has high specific capacity and high cycle stability.
[0080] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for rapidly preparing graphene, characterized in that: The following steps are involved: After the graphite oxide is pressed into shape, it is flash-burned to obtain the graphene; the flash-burning treatment comprises: placing the pressed graphite oxide on a conductive carrier, connecting the two ends of the conductive carrier to the positive and negative electrodes of a power source, and applying power to perform the flash-burning treatment; The temperature of the flash treatment is 1000-5000°C, and the holding time is 5-500s; the flash treatment is carried out under normal pressure; and the heating rate to the flash treatment temperature is 90-300°C / s.
2. The method according to claim 1, characterized in that The oxygen content of the graphite oxide is 0.1-30%.
3. The method according to claim 1, characterized in that The flash treatment is carried out in a protective atmosphere.
4. The method according to claim 1, characterized in that: Before the pressing and molding, the graphite oxide is ground; the particle size of the ground graphite oxide is 1-50 μm.
5. The method according to claim 1, characterized in that The pressing pressure is 18-24 MPa, and the holding time is 5-20 s.
6. The method according to claim 1, characterized in that The conductive carrier includes carbon paper, graphite sheet, molybdenum boat, tungsten boat or stainless steel sheet; The thickness of the conductive carrier is 0.1-10 mm.
7. The method according to claim 1, characterized in that The current of the power supply is 1~500A.
Citation Information
Patent Citations
Method for rapidly preparing graphene in large quantities by utilizing graphite oxides
CN102502611A
Flash joule heating synthesis method and compositions thereof
CN113165880A